3D printing of Fe-based bulk metallic glass composites with combined high strength and fracture toughness. (5th April 2018) - Li, Ning; Zhang, Jianji; Xing, Wei; Ouyang, Di; Liu, Lin
Abstract: Additive manufacturing is a promising technique for the production of bulk metallic glass (BMG) components without size limitations. However, the current additive manufacturing technique encounters the challenge of micro-cracking induced by huge thermal stress during the process, which significantly degrades the mechanical performance of the components. Based on systematic experiments combined with finite element simulation, we revealed that micro-cracks in inherently brittle Fe-based metallic glass during selective laser melting (SLM) are triggered by highly concentrated thermal stress around micro-pores, which is difficult to avoid during SLM even by careful process optimization. To suppress these micro-cracks, Cu and Cu-Ni alloys with high toughness as second phases were introduced to form BMG composites. The results revealed that the generation of high-density dislocations in second phases during SLM drastically reduce thermal stress by releasing strain energy and thus suppress micro-crack formation. Further investigation has shown that the introduction the second phase improves the fracture toughness of Fe-based BMGs to 47 MPa m 1/2, which is approximately 20 times higher than that of the Fe-based BMG (2.2 MPa m 1/2 ). Our findings provide general guidelines for the SLM fabrication of bulk metallic glass composites with tunable mechanical performances, as well as large sizes and freeform geometries. Graphical abstract: Highlights: Mechanism of micro-cracking in 3D printing brittle Fe-based metallic glass are analyzed. Micro-cracks were successfully suppressed in 3D printing Fe-based metallic glass. The mechanical properties 3D-printed Fe-based BMG composites can be optimized. The fracture toughness of the 3D printed Fe-based BMG composites increase 20 times.